GENERAL PRESENTATION OF REINFORCEMENT MODES OF THE RESISTANCE ELEMENTS - Catalina IANASI (Fiabilitate şi Durabilitate)
The reinforcement of the resistance structures, of the beam type, changed the way of their behavior, going from a fast destruction of the beam to a slower deterioration, thus increasing the load capacity of the beam. A problem that arises in these types of resistance elements remains the determination of the permissible breaking strength, given the bending stress, so that these elements can be used in a wide range of stresses and with the greatest possible applicability.